PERAN MEDIA SOSIAL “FACEBOOK” DALAM PROSES PEMBENTUKAN OPINI PUBLIK MENJELANG PEMILIHAN UMUM LEGISLATIF 2019 DI KABUPATEN ACEH JAYA - Aminah Aminah (SOURCE : Jurnal Ilmu Komunikasi, 2018)
This research aims to explain about to examine about the role of social media in making public decisions ahead of the legislative election 2019 in the district of Aceh Jaya. The data that is required in writing is obtained through library research and field. Library research done with how to read text books, legislation, and other reading material related to this research. While field research done by interviewing informants. The results of the study showed that the process of forming public opinion cannot be formed by itself. The process of forming public opinion consists of several stages, namely Phase I which is caused by several factors: cultural background, past, espoused values and news that develops. Stage 2 the formation of perception in the community, the third stage is formed, the fourth stage is the consensus, namely the last and last process or agreement on a public opinion. Through Facebook media, the process of forming public opinion is very fast. This happens to the maximum extent possible for people who use social media